Success at 100 is easier said than done – comments on Araújo et al: successful aging at 100 years. (19th January 2016) - Martin, Peter; Poon, Leonard W.
Abstract : Few would argue that achieving the age of 100 years is extraordinary, but what about the quality of life at this extreme age? Is it worth it to live to 100 and beyond? The study by Araújo, Ribero, Teixeira, and Paúl (2015 ) in three ways provided an answer to this question substantiating and complementing recent findings about successful aging in extreme old age (Poon and Perls, 2007 ; Martin et al ., 2015 ). First, the study joined other investigators in asking whether the criteria for successful aging posed by Rowe and Kahn (1997 ) are applicable for older adults at the end stage of a very long life. Second, the study shed light on whether objective or subjective criteria are more appropriate to gauge levels of successful aging for the oldest old (e.g. Pruchno et al ., 2010 ; Cho et al ., 2012 ). Finally, the study provided additional data on psychological, social, and economic resources that enhance the needed ingredients of successful aging at the century mark.